Bone marrow-derived extracellular vesicles from multiple myeloma patients promote adaptive immune dysfunction via HLA-G, PD-1, and PD-L1 - Soncini, Debora; Marimpietri, Danilo; Ladisa, Francesco; Lai, Francesco; Airoldi, Irma; Gramignoli, Roberto; Cea, Michele; Morandi, Fabio (Frontiers in Immunology, 2025)
IntroductionExtracellular vesicles (EVs) are critical mediators of intercellular communication and contribute to cancer progression and immune regulation.MethodsWe characterized EVs isolated from bone marrow (BM) plasma harvested from healthy donors and patients affected by Multiple Myeloma (MM) by Nano Tracking Analysis and by flow cytometry.ResultsEVs from MM patients were significantly more abundant and enriched in CD138, supporting their partial origin from malignant plasma cells, with additional input from BM resident cells, including monocytes and NK cells. Phenotypic profiling revealed increased expression of immune checkpoint molecules HLA-G, PD-1, and PD-L1 on MM-derived EVs compared to healthy controls. Functionally, MM-EVs suppressed Staphylococcal enterotoxin B (SEB)-induced T cell activation, as evidenced by reduced IFN-γ production and CD4+ T cell proliferation. Such effects were partially reversed by HLA-G blockade. Moreover, MM-derived EVs modulated cytokine secretion profiles suppressing IL-2, IFN-α, TNF-α, and IL-6, and enhancing GM-CSF, with some changes attributed to HLA-G and PD-L1 activity. Transcriptomic analysis showed higher HLA-G expression in patients with gain of chromosome 1q, suggesting a link between high-risk cytogenetics and EV-driven immune suppression. While clinical correlations were not observed, likely due to limited sample size, these findings underscore the immunosuppressive role of MM-derived EVs.DiscussionHLA-G+, PD-1+, and PD-L1+ EVs contribute to immune dysfunction in MM and represent promising targets to restore anti-tumor immunity.